2006
DOI: 10.1093/brain/awl050
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of tic generation in Tourette syndrome: an event-related functional MRI study

Abstract: Little is known about the neural correlates of tics and associated urges. In the present study, we aimed to explore the neural basis of tics in patients with Tourette syndrome by using event-related functional MRI (fMRI). Ten patients (6 women, 4 men; age: mean +/- SD = 31 +/- 11.2) were studied while spontaneously exhibiting a variety of motor and vocal tics. On the basis of synchronized video/audio recordings, fMRI activities were analysed 2 s before and at tic onset irrespective of the clinical phenomenolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
267
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(316 citation statements)
references
References 58 publications
29
267
2
4
Order By: Relevance
“…Furthermore, we also obtained ALEs for the peak activations associated with the urge to tic in individuals with TS reported by Bohlhalter et al (2006). These data are presented in Figure 5, which illustrates that all four behavioral domains overlap in the region of the mid-cingulate cortex and the insular cortex of the right hemisphere.…”
Section: Fmri and Anatomic Data Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…Furthermore, we also obtained ALEs for the peak activations associated with the urge to tic in individuals with TS reported by Bohlhalter et al (2006). These data are presented in Figure 5, which illustrates that all four behavioral domains overlap in the region of the mid-cingulate cortex and the insular cortex of the right hemisphere.…”
Section: Fmri and Anatomic Data Analysismentioning
confidence: 94%
“…One notable study was that reported by Hallett and colleagues, which used functional magnetic resonance imaging (fMRI) to examine brain areas activated immediately preceding the spontaneous occurrence of motor and/or vocal tics, and thus likely to be associated with the urge to tic (Bohlhalter et al, 2006). This study identified a network of brain areas that were activated immediately prior to tic onset, and, most importantly, identified the insular cortex, the anterior cingulate cortex, and the parietal operculum, which includes the secondary somatosensory cortex (SII) (Eickhoff, Amunts, Mohlberg, & Zilles, 2006), as the most likely anatomic regions responsible for the uncomfortable feelings associated with premonitory urges to tic (Bohlhalter et al, 2006). Consistent with this proposal, electrical stimulation of the insular cortex or the parietal operculum can elicit unpleasant somatosensory or visceral sensations (Augustine, 1996;Ostrowsky et al, 2002;Penfield & Faulk, 1955).…”
Section: Functional Anatomy Of Tics In Tsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 Both IMMP2L transcripts show high expression in the cerebellum, which is involved in TS pathogenesis. 34,35 Mitochondria dysfunction at the cellular level and cerebellum involvement at the anatomic level are also related to other movement disorders such as dystonia and ataxia. 36,37 It is therefore plausible that an unbalanced mitochondria function through a defective cerebellar IMMP2L may contribute to tic formation.…”
Section: Discussionmentioning
confidence: 99%